KEMAMPUAN MEMAHAMI KATA BAKU DAN PADANAN KATA PADA MAHASISWA AKTIF LULUSAN MATA KULIAH BAHASA INDONESIA - Shifa Harun Salsabilah; Talitha Dwi Aulia Rahmi; Ulfah Fauziah; Yuni Ertinawati (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
The background of this study is based on the loss of interest in the Indonesian language, resulting in a lack of understanding of standard words and their equivalents. The purpose of this study is to investigate the understanding of standard words and their equivalents in the Indonesian language. The method used is a qualitative approach through a descriptive research design, focusing on understanding the context and characteristics of the data. The data collection instrument is a Google Form questionnaire. The research sample consisted of 44 active students who had graduated from Indonesian language courses. The results showed that most students had an understanding of standard words. However, with a difference of 9.89%, students really needed to improve their understanding. Meanwhile, most students had an understanding of equivalent words. However, with a 36.3% difference, students needed to improve their understanding. These findings highlight the importance of language training and development for students to improve the effectiveness of Indonesian language learning and foster a positive attitude towards the language of science, a unifying tool, and national identity.